A new charismatic Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Southern India - Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Malzacher, Peter; Isack, Rajasekaran (Zootaxa, 2021)
Caenis americani sp. nov. is described based on larvae and female imagoes from the Mangalamkombu stream of Southern India. Caenis americani is most likely a parthenogenetic species, in the light of the fact that only females have been collected. The larva can be distinguished from other species of Caenis by the i) shape of the sternum IX and its shagreen field, ii) shape and denticulation of hind claws and iii) lateral lobes of mesonotum distinctly bulged. The phylogenetic relationships of the new species remain unknown, as molecular records of Caenis throughout the Oriental region are largely unknown, and the taxonomically important males are absent.